2003
DOI: 10.4049/jimmunol.170.7.3565
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 Mediates a More Potent Antiviral Response Than Toll-Like Receptor 4

Abstract: We have recently described an IFN regulatory factor 3-mediated antiviral gene program that is induced by both Toll-like receptor (TLR)3 and TLR4 ligands. In our current study, we show that activation of IFN/viral response gene expression in primary macrophage cells is stronger and prolonged with TLR3 stimulation compared with that of TLR4. Our data also reveal that the cytoplasmic tails of both TLR3 and TLR4 can directly interact with myeloid differentiation factor 88 (MyD88). However, although Toll/IL-1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
139
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 23 publications
10
139
2
1
Order By: Relevance
“…It is known that IFN-ß induces both TLR3 and CXCL10 mRNA leading to STAT1 phosphorylation on bone marrow macrophages (23). In the present study, we revealed that poly(I):poly(C) induced STAT1 activation on osteoblastic E1 cells and this effect was blocked by the addition of an anti-IFN-ß neutralizing antibody.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It is known that IFN-ß induces both TLR3 and CXCL10 mRNA leading to STAT1 phosphorylation on bone marrow macrophages (23). In the present study, we revealed that poly(I):poly(C) induced STAT1 activation on osteoblastic E1 cells and this effect was blocked by the addition of an anti-IFN-ß neutralizing antibody.…”
Section: Discussionsupporting
confidence: 54%
“…Our study revealed that poly(I):poly(C) up-regulated TLR3 expression in E1 cells. Doyle et al (23) reported that treatment of murine bonederived macrophages with a TLR3 ligand induced TLR3 mRNA expression. They also reported that stimulating macrophages with IFN-ß resulted in a dose-dependent upregulation of TLR3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIF, also known as TICAM-1 (TIR domain-containing adapter molecule 1), plays an essential role in TLR3-and TLR4-mediated interferon-b (IFN-b) activation through interferon regulatory factor 3/7 (IRF3/7)-dependent mechanism (Doyle et al, 2003;Fitzgerald et al, 2003). In piscine cells, both fugu Takifugu rubripes TLR3 (fgTLR3) and fgTLR22 employ the TRIF adaptor to induce IFN responses upon virus infection (Oshiumi et al, 2003;Matsuo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In the lifecycle of RNA viruses, double-stranded RNA (dsRNA) is generated and recognized by TLR3. 13,14 The activation of TLR3 results in the activation of interferon regulatory factor (IRF)-3, which is a key regulator of the induction of type I interferons (IFN), including IFN-␤, which are crucial mediators of the antiviral response. 15,16 Persistent HCV infection probably results from the disruption of host immune responses by HCV proteins.…”
mentioning
confidence: 99%